Applying The Ibrah Mauiẓah Method In Learning Qur'an Hadith At The Tsanawiyyah Level - Asep Abdul Aziz; Supiana Supiana; Muhibbin Syah; Hariman Siregar (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Islamic education is a subject that must be taught, either in public schools or Islamic boarding schools. Islamic boarding school is the oldest educational institution in Indonesia, which has an essential role in realizing the nation's character. The materials taught at Islamic boarding schools are related to Islamic education, including the Qur’an and Hadith, which need to be taught properly. Considering that today's Qu’ran-Hadith learning has not had a major impact on changing the nation's character, it is necessary to apply the right and inspiring method so that the expected results are not only cognitive. In this regard, the ibrah mauiẓah method is derived from the Qur'an, which is considered appropriate and soulful in providing the inculcation of Islamic values based on the Qur'an and Hadith. For this reason, this paper aims to develop the application of the ibrah mauiẓah method in learning the Qur’an-Hadith at the Tsanawiyyah level. The research methodology employed by the authors was a qualitative approach, with library research techniques in collecting data. The results revealed that applying the ibrah mauiẓah method has a spiritual nuance. When applied properly, it can increase the spiritual intelligence of students. Thus, it will have an impact on improving the character of students. Also, this application is divided into two stages: the pre-instructional and instructional stages.